Synthesis and Characterization of Open-Ring Polycomponent Complexes Formed in the Reaction of Lanthanides with m-Phenylenediamine and Dibenzoyl Methane - MEIYING, LI; PEIZHI, HU; WANREN, ZHU; YANG, WANG (Asian Journal of Chemistry, 2012)
Six new polycomponent complexes of lanthanides have been prepared by template reaction of m-phenylenediamine with dibenzoyl methane in the presence of lanthanide chlorides and conc. HCl in methanol solution. They have been characterized by elemental analysis, molar conductivity data, IR, UV, 1H NMR and TG-DTA. The measured results show that m-phenylenediamine is mono-condensed with dibenzoyl methane, forming a mono-condensate m-phenylenediaminediphenylpropane-1,3-dioneimine (L). The L is coordinated with lanthanide by carbonyl oxygen and azomethine nitrogen to form the complexes. The formula of the complexes is LnL2Cl3.2H2O, where Ln is Nd, Sm, Eu, Gd, Dy and Er, respectively.